Structural Characterization of a Covalent Monolayer Sheet Obtained by Two‐Dimensional Polymerization at an Air/Water Interface. (2nd November 2017) - Müller, Vivian; Shao, Feng; Baljozovic, Milos; Moradi, Mina; Zhang, Yao; Jung, Thomas; Thompson, William B.; King, Benjamin T.; Zenobi, Renato; Schlüter, A. Dieter
Abstract: This work describes a two‐dimensional polymerization at an air/water interface and provides, for the first time, direct spectroscopic evidence for the kind of crosslinks formed and for the conversion reached in a covalently bonded monolayer sheet. This evidence was obtained through a combination of a variety of monolayer characterization techniques before and after transfer onto solid substrates, in particular by tip‐enhanced Raman spectroscopy (TERS) and TERS mapping after transfer of both the monomer and polymer monolayer onto Au(111). This work is a major advance for the field of 2D polymers synthesized at the air/water interface as it, in principle, allows estimation of the crystallinity by percolation theory and the location of regions with defects.